Understanding preservation time thresholds in the modern era of heart transplantation - Chen Chia Wang; Jessica B. Briscoe; Corbin E. Goerlich; Rachael Quinn; Daniel Ragheb; Shivani Shirodkar; Antonio Polanco; Ahmet Kilic; Kavita Sharma; James Gammie; Ashish S. Shah; Chetan Pasrija (Scientific Reports)
Abstract A 4-h preservation time threshold for cardiac allografts is the current standard in heart transplantation, but novel technologies are proposed to decrease the morbidity associated with prolonged allograft storage. This study examined adult heart transplant recipients from 2000–2015 and 2020–2023 in the United States, stratified into an early (2000–2015) and modern era (2020–2023), then into standard (≤ 4 h) and prolonged (≥ 5 h) preservation time groups within each era. This study reinforced the 4-h threshold in the early era, where prolonged preservation significantly increased one-year mortality (HR 1.60, 95% CI 1.36–1.90). However, this association was no longer significant in the modern era (HR 1.14, 95% CI 0.85–1.50). A sub-analysis showed that using machine perfusion devices for allograft storage was not associated with one-year mortality (HR 1.15, 95% CI 0.79–1.70). Spline analysis demonstrated possible inflection points between 4 and 5 h and 8–9 h in the modern era, and further analysis found that 5–8 h of preservation did not increase one-year mortality (HR 1.09, 95% CI 0.80–1.47) relative to the ≤ 4 h group. In conclusion, the association between cardiac allograft preservation duration and morbidity has decreased in the modern era. Today, a 4-h preservation duration threshold may be too restrictive.